Culture Shock Experienced by the Main Character in the Picture Book The Way We Do It in Japan - Loviana Ressyanti; Yosep Bambang Margono Slamet (International Journal of Multilingual Education and Applied Linguistics, 2026)
Culture shock is a phenomenon commonly experienced by individuals who encounter unfamiliar cultural environments, including children. This phenomenon is represented in the picture book The Way We Do It in Japan through the experiences of Gregory, an Asian-American child who moves from America to Japan and faces cultural differences in daily life. This study aims to analyze the representation of cultural differences between Japan and America and to examine the stages of culture shock experienced by Gregory throughout the story. This study employs a descriptive qualitative method using textual and visual analysis of the picture book. The analysis applies Oberg’s (1960) concept of culture shock and Pedersen’s (1995) stages of culture shock, including the honeymoon, disintegration, reintegration, autonomy, and interdependence stages. The findings reveal that differences in language, social norms, daily habits, and school practices become the main triggers of Gregory’s culture shock. His experiences develop dynamically from curiosity and confusion to gradual adaptation and cultural acceptance. These experiences also contribute to Gregory’s emotional growth, adaptability, and ability to understand cultural differences more objectively. Therefore, this study highlights the important role of children’s literature in promoting intercultural understanding, empathy, and awareness of cultural diversity among young readers.